Plant breeding: a long-term strategy for the control of zinc deficiency in vulnerable populations - Ruel, Marie T.; Bouis, Howarth E. (International Food Policy Research Institute, 1997)
Because trace minerals are important not only for human nutrition, but for plant nutrition as well, plant breeding holds great promise for making a significant low-cost and sustainable contribution to reducing micronutrient deficiencies in humans, and may have important spinoff effects for increasing farm productivity in developing countries in an environmentally beneficial way. This paper describes ongoing plant breeding research that could increase the intake of bioavailable zinc from food staple crops among vulnerable populations in developing countries. The three most promising plant breeding strategies to achieve this goal are (1) increasing the concentration of zinc in the plant, (2) reducing the amount of phytic acid (a strong inhibitor of zinc absorption), and (3) raising the levels of sulfur-containing amino acids (which are thought to promote zinc absorption). The agronomic advantages and disadvantages as well as the potential benefits and limitations of each approach for human nutrition are described. Research is currently underway to identify the optimal combination of these approaches that will maximize impact on human zinc nutrition.